2010
DOI: 10.1128/jb.01471-09
|View full text |Cite
|
Sign up to set email alerts
|

Archaeal Eukaryote-Like Serine/Threonine Protein Kinase Interacts with and Phosphorylates a Forkhead-Associated-Domain-Containing Protein

Abstract: Protein phosphorylation plays an important role in cell signaling. However, in the Archaea, little is known about which proteins are phosphorylated and which kinases are involved. In this study, we identified, for the first time, a typical eukaryote-like Ser/Thr protein kinase and its protein partner, a forkhead-associated (FHA)-domain-containing protein, from the archaeon Sulfolobus tokodaii strain 7. This protein kinase, ST1565, physically interacted with the FHA-domain-containing protein, ST0829, both in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 39 publications
2
21
0
Order By: Relevance
“…2010). All of them contained the catalytic loop (DVKPSN), the DFG motif and the conserved residues K 166 , D 287 and D 314 known from classical eukaryotic homologs (see Fig.…”
Section: Ser Thr and Tyr Phosphorylation In Archaeamentioning
confidence: 99%
“…2010). All of them contained the catalytic loop (DVKPSN), the DFG motif and the conserved residues K 166 , D 287 and D 314 known from classical eukaryotic homologs (see Fig.…”
Section: Ser Thr and Tyr Phosphorylation In Archaeamentioning
confidence: 99%
“…Moreover, at least one of the eight potential ePKs identified, the protein product of st1565, resembles the typical ePKs that predominate in eukaryotes (54). Using two-hybrid screens and pulldown assays, it was determined that the ST1565 protein kinase complexes with the protein product of st0829, a forkhead-associated (FHA) domain-containing transcription factor that interacts with the promoter region of a gene cluster encoding flagella-like proteins (55).…”
Section: The Sulfolobales Kinomementioning
confidence: 99%
“…The FHA domain-containing protein was initially implicated by its capacity to bind to and to physically interact with a typical ePK, the product of ORF st1565 from S. tokodaii (54). Subsequent analysis quickly revealed that the FHA domain-containing protein was phosphorylated by the ST1565 ePK in vitro, although the identity and location of the amino acid residue modified were not determined.…”
Section: The Sulfolobales Phosphoproteomementioning
confidence: 99%
“…St0829 of Sulfolobus tokodaii was demonstrated to be a Ser/Thr‐specific kinase that phosphorylates the forkhead‐associated (FHA) domain‐containing protein St1565. Unphosphorylated St1565 binds to the promoter region of the operon encoding the archaellum, while phosphorylation inhibits binding (Duan & He, ; Wang, Yang, Zhang, & He, ). However, the physiological function of this kinase remains unclear.…”
Section: Introductionmentioning
confidence: 99%